Birthing life and death: women’s reproductive health in early twentieth-century Rio de Janeiro - Cassia Roth (História, Ciências, Saúde: Manguinhos)
Abstract This article explores women’s reproductive health in early twentieth-century Rio de Janeiro, showing that elevated and sustained stillbirth and maternal mortality rates marked women’s reproductive years. Syphilis and obstetric complications during childbirth were the main causes of stillbirths, while puerperal fever led maternal death rates. Utilizing traditional sources such as medical dissertations and lesser-used sources including criminal investigations, this article argues that despite official efforts to medicalize childbirth and increase access to clinical healthcare, no real improvements were made to women’s reproductive health in the first half of the twentieth century. This, of course, did not make pregnancy and childbirth any easier for the women who embodied these statistics in their reproductive lives.